Actual Aspects of Surgical Treatment of Dupuytren’s Disease (Literature Review) - Naumenko, L.Yu.; Kondrashova , I.A. (TERRA ORTHOPAEDICA, 2021)
Relevance. The variety of manifestations of Dupuytren’s disease, caused by the degree of lesions of the palmar aponeurosis, the duration of the disease, the nature of professional activity, and concomitant pathology of patients, has led to the development of numerous surgical techniques with different levels of effectiveness in the acute and long-term periods. A wide discussion of the issues of Dupuytren’s disease in the domestic and foreign periodicals, the analysis of treatment methods, complications and rehabilitation indicate the urgency of the problem and the expediency of further research. Objective: a retrospective analysis of the leading literary sources devoted to the surgical treatment of Dupuytren’s disease; the definition of modern approaches to surgical tactics and restoration of hand function. Results. The analysis of literature sources showed the advantages of differentiated approaches to the surgical treatment of Dupuytren’s disease, depending on the severity of the disease. With mild and moderate lesions, there is a significant increase in needle aponeurectomy. In severe forms, the segmental aponeurectomy technique is preferred over the total one. There is some discrepancy in carrying out surgical mobilization of the proximal interphalangeal joint and the need to achieve a functional position as a result of treatment. The tactics of surgical treatment and rehabilitation of Dupuytren’s disease requires an individual approach, taking into account the age and severity of the disease, and tends to spread minimally invasive fasciotomy techniques.